2016
DOI: 10.1155/2016/1864039
|View full text |Cite
|
Sign up to set email alerts
|

Bark Thickness Equations for Mixed-Conifer Forest Type in Klamath and Sierra Nevada Mountains of California

Abstract: We studied bark thickness in the mixed-conifer forest type throughout California. Sampling included eight conifer species and covered latitude and elevation gradients. The thickness of tree bark at 1.37 m correlated with diameter at breast height (DBH) and varied among species. Trees exhibiting more rapid growth had slightly thinner bark for a given DBH. Variability in bark thickness obscured differences between sample locations. Model predictions for 50 cm DBH trees of each species indicated that bark thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…Bark thickness, on the other hand, increased with DBH and decreased with relative height up the stem. Bark thickness is known to increase with tree age (Cellini et al 2012;Williams et al 2007) and, consequently, with tree diameter (Chowdhury et al 2013;Nefabas and Gambiza 2007;Sonmez et al 2007;Williams et al 2007;Zeibig-Kichas et al 2016). As in this study, Williams et al (2007) found that the bark was thicker at lower portion of the stem for six South African tree species.…”
Section: Discussionsupporting
confidence: 66%
“…Bark thickness, on the other hand, increased with DBH and decreased with relative height up the stem. Bark thickness is known to increase with tree age (Cellini et al 2012;Williams et al 2007) and, consequently, with tree diameter (Chowdhury et al 2013;Nefabas and Gambiza 2007;Sonmez et al 2007;Williams et al 2007;Zeibig-Kichas et al 2016). As in this study, Williams et al (2007) found that the bark was thicker at lower portion of the stem for six South African tree species.…”
Section: Discussionsupporting
confidence: 66%
“…After including these influential tree variables in the BT regressions, other factors explaining additional variation in BT included genotype, stand structure (BT ranked even-aged < multiaged), and geographic region (BT ranked north < central < southern regions). The regional variation in BT has also been detected among Sierra Nevada conifers throughout California [12] but not white spruce (Picea glauca) across Alaska [32].…”
Section: Discussionmentioning
confidence: 85%
“…The strong correlation between tree size and BT signals potential to increase BT by thinning to enhance the tree diameter growth. However, there is some evidence that slower growing trees have a thicker bark relative to their diameter, suggesting that BT is also dependent on tree age [12]. Site quality and soil fertility may influence BT directly, or indirectly by affecting the tree growth rates [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fire effects model documentation indicates that the relationship between DBH and bark thickness is assumed to be linear: while a common simplification, this is rarely the case, and has not been established for Oregon white oak (Jackson et al 1999). Other studies have found that these models can underpredict bark thickness, potentially leading to overestimation of mortality in fires (Zeibig-Kichas et al 2016;Kane et al 2017). Moreover, FOFEM employs a common bark thickness coefficient for all oak species, an assumption that likely adds considerable error to the model.…”
Section: Discussionmentioning
confidence: 99%